2003
DOI: 10.1257/000282803769206205
|View full text |Cite
|
Sign up to set email alerts
|

On the Evolution of the Firm Size Distribution: Facts and Theory

Abstract: Using a comprehensive data set of Portuguese manufacturing firms, we show that the firm size distribution is significantly right-skewed, evolving over time toward a lognormal distribution. We also show that selection accounts for very little of this evolution. Instead, we propose a simple theory based on financing constraints. A calibrated version of our model does a good job at explaining the evolution of the firm size distribution. (JEL L11)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

65
600
6
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 784 publications
(678 citation statements)
references
References 13 publications
65
600
6
7
Order By: Relevance
“…Particularly the indigenous sectors has a large number of very small firms, some of which have received grant support. Job additionality effects for these may be very different than for larger firms, particularly since small firms tend to be more financially constrained; see Cabral and Mata (2003). As a matter fact, Lehinan (2004) shows from an analysis of a selective questionnaire that support of smaller Irish firms is less likely to cause deadweight loss.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly the indigenous sectors has a large number of very small firms, some of which have received grant support. Job additionality effects for these may be very different than for larger firms, particularly since small firms tend to be more financially constrained; see Cabral and Mata (2003). As a matter fact, Lehinan (2004) shows from an analysis of a selective questionnaire that support of smaller Irish firms is less likely to cause deadweight loss.…”
Section: Resultsmentioning
confidence: 99%
“…A strand of the empirical literature has thus sought to examine the application of lognormal and Pareto or power-law distributions using firm size data as cross-sectional data [13] [14] [15]. However, there is evidence that, on some occasions, a poor approximation of the empirical distributions of the firm size in the upper tail, which typically exhibit greater asymmetry as a small number of large firms exist alongside a large number of smaller firms [1] [12] [16], is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The differences obtained in applying these types of firm size distributions have led researchers in this area to discuss the stability of a single firm size probability model over time and across industries and countries [5] [17] [13] [14] [18]. These discrepancies likely occur because the distributions that are traditionally used to model data with very thick tails have the disadvantage of relying on very few parameters for capturing the entire shape of the firm size distribution, including its right tail [18].…”
Section: Introductionmentioning
confidence: 99%
“…In another study on Italian firms, the findings by Cabral and Mata [13] have been confirmed, using the generalized Beta distribution of the second kind. In this regards, the size distribution of Italian firms is approximated by a Singh-Maddala distribution for the youngest firms and a Fisk one for the oldest ones [14].…”
Section: Literaturementioning
confidence: 69%
“…Among several studies in industrial economies on the determinants of firm size distribution, some of them considered the effect of age.In general, as the age of the firms increases, the size distribution shifts to the right, the left tails become thinner and the right tail thicker, with a clear decrease of the skewness [13]. In another study on Italian firms, the findings by Cabral and Mata [13] have been confirmed, using the generalized Beta distribution of the second kind.…”
Section: Literaturementioning
confidence: 82%